Strategi Pengelolaan Badan Usaha Milik Desa dalam Meningkatkan Perekonomian Masyarakat di Desa Kutamaneuh Kecamatan Tegalwaru Kabupaten Karawang - Devi Sri Rahayu; Dadan Kurniansyah; Rachmat Ramdani (Peneliti.net, 2022)
This study discusses the Strategy for Management of Village Owned Enterprises (Bumdes) in Improving the Community Economy in Kutamaneuh Village, Tegalwaru District, Karawang Regency. This study uses a qualitative descriptive method with data collection techniques carried out through the triangulation stages, namely interviews, observations and documentation studies. Then the data that has been obtained is analyzed through three stages of reduction, presentation and conclusion. The results of this study indicate that the Village Bumdes of Kutamaneuh Village has formulated two strategic formulations, namely LPG gas and hajat rental. Meanwhile, in the implementation of the Bumdes strategy in Kutamaneuh Village, there are still obstacles in the human resources department. Meanwhile, for the evaluation of the strategy, it was found that there was inconsistency between village officials who always thought that the strategy had been running optimally, so that corrective steps were not carried out routinely